Antibiotic Utilization Patterns for Different Wound Types among Surgical Patients: Findings and Implications - Zikria Saleem; Umar Ahsan; Abdul Haseeb; Ummara Altaf; Narjis Batool; Hira Rani; Javeria Jaffer; Fatima Shahid; Mujahid Hussain; Afreenish Amir; Inaam Ur Rehman; Umar Saleh; et al. (Antibiotics, 2023)
Antimicrobial prophylaxis is effective in reducing the rate of surgical site infections (SSIs) post-operatively. However, there are concerns with the extent of prophylaxis post-operatively, especially in low- and middle-income countries (LMICs). This increases antimicrobial resistance (AMR), which is a key issue in Pakistan. Consequently, we conducted an observational cross-sectional study on 583 patients undergoing surgery at a leading teaching hospital in Pakistan with respect to the choice, time and duration of antimicrobials to prevent SSIs. The identified variables included post-operative prophylactic antimicrobials given to all patients for all surgical procedures. In addition, cephalosporins were frequently used for all surgical procedures, and among these, the use of third-generation cephalosporins was common. The duration of post-operative prophylaxis was 3–4 days, appreciably longer than the suggestions of the guidelines, with most patients prescribed antimicrobials until discharge. The inappropriate choice of antimicrobials combined with prolonged post-operative antibiotic administration need to be addressed. This includes appropriate interventions, such as antimicrobial stewardship programs, which have been successful in other LMICs to improve antibiotic utilization associated with SSIs and to reduce AMR.